INTEGRATED NEUROMUSCULAR INHIBITION TECHNIQUE LEBIH MENINGKATKAN LINGKUP GERAK SENDI LEHER DARIPADA CONTRACT RELAX STRETCHING PADA KASUS SINDROM MYOFASCIAL OTOT UPPER TRAPEZIUS - Putu Ayu Sita Saraswati; Ni Komang Juni Antari; Anak Agung Gede Angga Puspa Negara (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT``Myofascial pain syndrome in upper trapezius muscle is a muscle pain that implicated by one or somemyofascial trigger points in upper trapezius muscle. Working with static position in long time stimulating the presence ofmyofascial trigger points that causing pain and movement limitation of the neck that stimulate neck disability. Physicaltherapy’s intervention for reducing pain in this case could be integrated neuromuscular inhibition technique or contractrelax stretching combined with ultrasound modality. Purpose: to compare the both interventions in reducing neckdisability of myofascial pain syndrome in upper trapezius muscle. Method: this was an experimental study withRandomized Pre and Post Test Group Design. Samples were divided into 2 treatment group that consist 12 samplesfor each group. The first group treated with integrated neuromuscular inhibition technique with ultrasound while thesecond group treated with contract relaxes stretching with ultrasound. The data was collected by measuring neck rangeof motion using goniometer at the time before and after treatment. Result: the 1st group showed that the Neck ROMincrease 5.083±1.0840 (p<0.001) and the 2nd group showed that the Neck ROM increase 3.333±0.7780(p<0.001). Itmeans there were significant effect of each treatment in both groups. The results of independent t-test showed p<0.001,so that there was significant difference of increased Neck ROM between these groups. The result of independent t-testshowed p value 0.001, so there was significant difference between two groups at increasing neck ROM. Conclusion:combination integrated neuromuscular inhibition technique is more effective than contract relax stretching to ultrasoundmodality in increasing neck range of motion of myofascial syndrome in upper trapezius muscle.Keywords: myofascial, neck disability, trapezius, INIT, ultrasound, stretching